PENGARUH KOMPENSASI, DISIPLIN KERJA DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PT. SGN PABRIK GULA ASSEMBAGOES DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Dian Prihatin Ningrum; Yudha Praja; Rini Kartika Sari (Fakultas Ekonomi dan Bisnis, 2025)
Entering the era of the Industrial Revolution, changes in Human Resources (HR) have occurred alongside rapid industrial advancement. Human Resources plays a crucial role in the continuity of a company’s operations. Given the significance of HR as a fundamental asset, companies are required to develop and manage HR effectively. Empowering and motivating human resources is a strategic approach that enables companies to grow and compete effectively with other industry players. This study aims to examine the effects of compensation, work discipline, and work culture on performance, with job satisfaction as an intervening variable, at PT. SGN Assembagoes Sugar Factory, Asembagus District, Situbondo Regency. The sampling technique used in this study is total sampling, involving all 70 employees of PT. SGN Assembagoes Sugar Factory as research participants. Data analysis and hypothesis testing were conducted using Structural Equation Modeling - Partial Least Squares (PLS-SEM). The results of hypothesis testing using Smart PLS 4.0 indicate that compensation has a significant positive effect on job satisfaction, work discipline has a significant positive effect on job satisfaction, and work culture also has a significant positive impact on job satisfaction. Moreover, compensation has a significant positive effect on performance, while work discipline and work culture have a positive but not significant impact on performance. Job satisfaction has a significant positive effect on performance. Furthermore, compensation has a positive but not significant indirect effect on performance through job satisfaction. In contrast, both work discipline and work culture have substantial positive indirect effects on performance through job satisfaction.